2015
DOI: 10.1182/blood.v126.23.848.848
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Signaling Has a Critical Role in Maintaining Regulatory T Cell Homeostasis; Implication for Treg Depletion Therapy By PD-1 Blockade

Abstract: CD4+ Foxp3+ regulatory T cells (Treg) play a central role in the maintenance of immune tolerance. In the setting of allogeneic hematopoietic stem cell transplantation (HSCT), Treg recovery after transplant has been reported as a critical factor to suppress the onset of graft-versus-host disease (GVHD) and stabilize the immune condition. We previously demonstrated that low-dose IL-2 administration preferentially increased Treg in patients with active chronic GVHD and resulted in clinical improvement of the symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Furthermore, PD-1 may suppress the proliferation of T regulatory cells (Tregs). The blockade of PD-1 may promote the proliferation of Tregs that leads to increased immunosuppression, hence the reactivation of HBV [23, 24]. In line with these inconsistent hypotheses, the only clinical trial with anti-PD-1 antibody for non-cancer patients with viral hepatitis showed that even though some patients have persistent suppression of HCV replication, only 5 of 42 patients (12%) met the primary endpoint of a ≥ 0.5 log reduction in HCV RNA [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PD-1 may suppress the proliferation of T regulatory cells (Tregs). The blockade of PD-1 may promote the proliferation of Tregs that leads to increased immunosuppression, hence the reactivation of HBV [23, 24]. In line with these inconsistent hypotheses, the only clinical trial with anti-PD-1 antibody for non-cancer patients with viral hepatitis showed that even though some patients have persistent suppression of HCV replication, only 5 of 42 patients (12%) met the primary endpoint of a ≥ 0.5 log reduction in HCV RNA [25].…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4 + Tregs increase during HIV infection [ 9 , 16 , 17 ] and remains higher despite antiretroviral therapy (ART) [18] . PD1 is expressed on Tregs under resting and activated conditions [ 19 , 20 ] and prevents the proliferation and immune responses of effector T-cells [ 21 , 22 ]. Untreated HIV infection increases PD1 + Tregs, and their levels positively correlate with viral load and exhaustion of total CD4 and CD8 T-cells [23] .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, Tregs also express PD-1, which affected their homeostasis ( 17 , 220 ). PD-1 also is thought to participate in Treg suppression ( 221 ).…”
Section: Therapies Targeting Treg Functionmentioning
confidence: 79%